2019
DOI: 10.1101/735340
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Superior Colliculus to VTA pathway controls orienting response to conspecific stimuli

Abstract: Social behaviors are highly important in mammals as conspecific interaction impairments are symptomatic of neuropsychiatric diseases. Several neural circuit mechanisms underlying the regulation of social behaviors have been described. Among them, dopamine (DA) neurons in the Ventral Tegmental Area (VTA) have been implicated in modulating the rewarding properties of conspecific interaction. However, how DA neurons receive information related to conspecifics is still an open question. In this study, we identifie… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Recently, it has been shown that flight-to-shelter responses to looming stimuli are mediated by VTA GABAergic neurons and driven by excitatory projections from the ventral superior colliculus (vSC) (Zhou et al, 2019). This projection innervates both dopaminergic and GABAergic neurons in the VTA (Prévost-Solié et al, 2019; Zhou et al, 2019) and additionally regulates orientation during social interaction (Prévost-Solié et al, 2019). In order to determine if the vSC can induce dopaminergic neurotransmission in a manner similar to overhead light exposure, we stereotaxically injected an AAV vector (AAV5-hSyn-ChR2(H134R)-eYFP) into the vSC to express the light-gated ion channel channelrhodopsin-2 (ChR2) in neurons, followed by implantation of an optical fiber for 473 nm light delivery in C57Bl/6N mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been shown that flight-to-shelter responses to looming stimuli are mediated by VTA GABAergic neurons and driven by excitatory projections from the ventral superior colliculus (vSC) (Zhou et al, 2019). This projection innervates both dopaminergic and GABAergic neurons in the VTA (Prévost-Solié et al, 2019; Zhou et al, 2019) and additionally regulates orientation during social interaction (Prévost-Solié et al, 2019). In order to determine if the vSC can induce dopaminergic neurotransmission in a manner similar to overhead light exposure, we stereotaxically injected an AAV vector (AAV5-hSyn-ChR2(H134R)-eYFP) into the vSC to express the light-gated ion channel channelrhodopsin-2 (ChR2) in neurons, followed by implantation of an optical fiber for 473 nm light delivery in C57Bl/6N mice.…”
Section: Resultsmentioning
confidence: 99%
“…Adult and adolescent human subjects with NF1 exhibit visual processing deficits (Hyman et al, 2005), although visual cortical areas have sparse, if any, direct connections to VTA dopaminergic neurons (Watabe-Uchida et al, 2012). Short latency dopaminergic responses to visual stimuli are likely driven by afferents from the superior colliculus (SC) (Redgrave et al, 2010), which receives direct input from retinal ganglion cells (Dhande and Huberman, 2014), responds to looming stimuli (Zhao et al, 2014), and evokes firing of both VTA GABAergic and dopaminergic neurons in vivo while enhancing flight-to-shelter responses (Prévost-Solié et al, 2019; Zhou et al, 2019). Because the dopaminergic response to optogenetic vSC stimulation occurred at stimulus onset, quickly attenuated, and was followed by a post-stimulation rebound, it is likely that excitatory vSC-to-VTA projections excite and subsequently suppress dopaminergic outflow via feed-forward inhibition, producing rebound disinhibition at stimulus offset.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, excitatory inputs from the DCN to VTA neurons have been identified as an important pathway involved in the control of social reward 6 . More recently, the superior colliculus to VTA-Dorsal Striatum circuit has been proposed to regulate the orientation towards an unfamiliar conspecific mouse while the anterior cortex to VTA-NAc pathway would be involved in the modulation of conspecific interaction without affecting orienting behaviors 67 . Interestingly, our results indicate that the regulation of pro-social behavior relied in part of DA signaling within the CC.…”
Section: Discussionmentioning
confidence: 99%
“…(behaviour) Unilateral manipulation of excitatory SC input to the VTA modifies orienting towards conspecifics (Prévost-Solié et al, 2019), and bilateral activation and inhibition of SC inputs to the SNc facilitate and impair hunting behaviour respectively (Huang et al, 2021). Inhibiting SC input to the SNc does not affect escape responses to visual threats, suggesting a specialised role.…”
Section: Basal Gangliamentioning
confidence: 99%